2007
DOI: 10.4070/kcj.2007.37.5.187
|View full text |Cite
|
Sign up to set email alerts
|

High Density Lipoprotein Cholesterol Comes of Age

Abstract: Despite the excellent success of lowering low-density lipoprotein cholesterol (LDLc) cholesterol for treating coronary heart disease (CHD), a major part of the population still suffer from CHD. This fact is more prominent among the high risk patients who receive lipid lowering treatment with statins. This treatment is based on the prevailing view that LDL cholesterol (LDLc) is the only important risk factor for CHD. It is well known that HDL plays a crucial role for preventing CHD. Several epidemiologic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The sample was housed in a glass capillary tube in direct contact with the flowing helium vapor. A Bruker NMR spectrometer with a home-built probe and solenoidal coil [32] were used for NMR detection. Microwave irradiation was provided through a 90 mW Gunn diode source (Millitech), and the µWs were coupled from room temperature to the sample via a mm waveguide and horn antenna.…”
mentioning
confidence: 99%
“…The sample was housed in a glass capillary tube in direct contact with the flowing helium vapor. A Bruker NMR spectrometer with a home-built probe and solenoidal coil [32] were used for NMR detection. Microwave irradiation was provided through a 90 mW Gunn diode source (Millitech), and the µWs were coupled from room temperature to the sample via a mm waveguide and horn antenna.…”
mentioning
confidence: 99%
“…This might give an indication to a good lipidemia control among Chinese as HDL is considered a cardio protective lipoprotein and according to ADA and Malaysian-MOH guidelines, rising HDL level is the second strategy in the treatment of diabetes dyslipidemia. [34][35][36] Limitations of the study As a retrospective data was unavailable to identify the BMI influence on individual subject. The subjects were enrolled according to the completeness of medical profile, so this can cause a possible bias in term of selecting the subjects with incomplete medical follow-up/record.…”
Section: Discussionmentioning
confidence: 99%
“…This might give an indication to a good lipidemia control among Chinese as HDL is considered a cardio protective lipoprotein and according to ADA and Malaysian-MOH guidelines, rising HDL level is the second strategy in the treatment of diabetes dyslipidemia. 3436…”
Section: Discussionmentioning
confidence: 99%
“…High-density lipoprotein (HDL) is the particle transporting cholesterol from peripheral tissues to liver and thus high-density lipoprotein-cholesterol (HDL-C) has been considered as a major negative risk factor for coronary heart disease. 1) In Framingham study, 12 years of follow-up showed a significant HDL-C effect on total and cardiovascular (CV) mortality. 2) Not only epidemiologic studies but also clinical trials such as the Veterans Affairs High-density lipoprotein Intervention Trial (VA-HIT) suggested the beneficial effect of raising HDL-C. 3) Not only the direct effect, the role of HDL-C as a modifying factor of statin effect has been also reported.…”
mentioning
confidence: 99%